Infants' Perception of the Intonation of Broad and Narrow Focus. Issue 1 (2nd January 2016) - Butler, Joseph; Vigário, Marina; Frota, Sónia
ABSTRACT: Infants perceive intonation contrasts early in development in contrast to lexical stress but similarly to lexical pitch accent. Previous studies have mostly focused on pitch height/direction contrasts; however, languages use a variety of pitch features to signal meaning, including differences in pitch timing. In this study, we investigate infants' perception of the prosodic contrast that cues the difference between all-new information (broad focus) and the highlighting of a particular word (narrow/contrastive focus) in European Portuguese (EP), and which has been described as having pitch timing as its key feature. Using a modified version of the visual habituation paradigm, EP learning infants discriminated this contrast at 12 months but not at 7 months, deviating from previous findings of a precocious ability to perceive pitch distinctions. These results suggest different developmental trajectories of the perception of different prosodic contrasts, underlining the importance of the nature of the cues signalling a given contrast in a given language.